Analisis Kinerja Keuangan Pada Industri Property dan Real Estate Serta Kontribusinya Terhadap Pendapatan Negara Dari Sektor Pajak - Ferina, Veren; Amrulloh, Amrulloh (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
The global economy is currently experiencing a shocking crisis. Many people, particularly entrepreneurs, are affected by this condition. This compels companies in Indonesia to maintain their good performance in order to be able to compete and survive. Company performance can be identified and assessed through analysis on the company's financial statements. The financial statements consist of the Statement of Financial Position, the Profit and Loss Statement, the Equity Change Report, the Cash Flow Statement, and the Notes to Financial Statements. With the analysis of financial statements, the performance of an enterprise can be assessed by performing a mathematical calculation of the items in the financial statements. In addition to examining the company's performance, financial statement analysis can also predict the company's financial condition in the future. It also serves as the source of information about the company's health condition. This financial statement analysis is very useful as information for various parties, such as the government, investors, and other users of financial statements to assess the financial condition of a company. The purpose of this study was to determine the financial performance of property and real estate companies as well as their contributions to the state from the tax sector. The research was conducted by taking financial statements from property and real estate companies listed on the Indonesia Stock Exchange in 2016-2018. The results show that the property and real estate companies with the best financial performance was Bumi Serpong Damai Tbk. In terms of contributions made by companies from the tax sector, Pakuwon Jati Tbk has contributed increasingly consistent every year. However, if seen from its financial performance, Bumi Serpong Damai Tbk has the best performance and good tax contributions. Key words :Analysis of Financial Performance and Tax Contributions.